Compliance - Bacigalupo, Silvina (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
Compliance originated in the Spanish legal discourse as result of an amendment to the Spanish Criminal Code that introduced the criminal liability of legal persons and corporations in 2010. Furthermore, in 2015, the possibility of compliance programs being caused by an exemption of the criminal liability of legal persons and corporations was introduced. The term comes from Anglo-Saxon law: Following the political and financial scandals of the 80’s and 90’s, laws were passed that demand more efficacy of private corporations as agencies of prevention of bribes of officials and politicians –see Watergate– could be detected. Currently, however, compliance has assumed a greater dimension destined not only to the prevention of bribes, but also to all crimes that could be committed in the realm of corporate activities in general and as a program of corporate culture and culture of legality. This essay analyzes different legal aspects of compliance and arrives at the conclusion that there cannot be any such thing as a corporate culture if not based on the adherence to the law.
Keywords: Compliance, corporate culture, compliance and criminal liability of corporations, compliance program, compliance officer, prevention of crimes, prevention of corruption, compliance in the public sector